The Contribution of the Student’s Collocation Mastery to Vocabulary Mastery - ERLINNA JUITA (LINGUA LITERA : journal of english linguistics and literature, 2015)
Collocation is one of the aspects affecting vocabulary mastery. However, the knowledge which the students had in collocation was not in line with theunderstanding and use of the single words. Therefore, they had difficulties in using and choosing the appropriate words in different contexts of communication. In order to know the contribution of collocation to the students‟ vocabulary mastery, a test of collocation and a test of vocabulary mastery which included collocation as part of it were applied as the instruments of the research. The sample of the research was selected by applying cluster random sampling. This study proved that the collocation contributes significantly to the student‟s vocabulary mastery. Therefore, collocation and vocabulary mastery could not be treated separately in vocabulary learning and teaching.